ANTI-INFLAMMATORY EFFECT OF CHLOROFORM EXTRACT OF FLAVERIA TRINERVIA (SPRENGEL) C. MOHR -A MEDICINAL HERB. - M. MALATHI; M .S. SUDARSHANA; M. H. NIRANJAN (International Journal of Pharma and Bio Sciences, 2012)
In the present study of chloroform extract of leaves of Flaveria trinervia (Sprengel) C.Mohr. (Asteraceae) obtained by soxhlet extraction method was tested for anti-inflammatory activity by carrageenan induced paw edema in rats. The chloroform extract in dose of 250mg /kg b.w was administered orally.Anti- inflammatory activity effect was compared with standard drug – Indomethacin (10mg/kg b.w) showed 31% and 51% inhibition of paw edema, in extract and standard respectively. These observations help us to conclude that chloroform extract has showed good anti- inflammatory activity against carrageenan induced paw edema.